Combined Effect of Incinerated Biomedical Waste Ash and Pond Ash On the Properties of Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete is one of the most widely used  construction materials, but its production contributes to  significant environmental concerns due to the high  consumption of natural resources and the generation of  large amounts of waste. In recent years, efforts have been  made to incorporate industrial by-products, such as fly ash  and slag, into concrete to enhance its sustainability and  performance. This research paper investigates the combined  effect of incinerated biomedical waste ash (IBWA) and  pond ash (PA) as supplementary cementitious materials on  the properties of concrete. The study involves an  experimental investigation conducted to evaluate the fresh  and hardened properties of concrete incorporating different  proportions of IBWA and PA. Concrete mixes with varying  replacement levels of cement by IBWA and PA are  prepared and their workability, compressive strength, split  tensile strength and flexural strength are examined. The  results reveal that the compressive strength, split tensile  strength and flexural strength of the concrete specimens are  found to increase up to a certain replacement level and then  gradually decrease. The improvements in concrete  properties can be attributed to the pozzolanic and filler  effects of IBWA and PA, which contribute to the formation  of additional hydration products and denser microstructures.  This research provides valuable insights into the potential  utilization of incinerated biomedical waste ash and pond ash  as sustainable alternatives to conventional cement in  concrete production. The findings highlight the feasibility  of reducing the environmental impact associated with the  disposal of wastes while simultaneously enhancing the  performance of concrete. The outcomes of this study can be  instrumental in promoting the adoption of environmentally friendly practices in the construction industry and  facilitating the development of guidelines for incorporating  IBWA and PA in concrete mix designs.
Keywords: Concrete; incinerated biomedical waste ash; Pond ash; sustainable materials; supplementary cementitious materials; compressive strength; flexural strength; split tensile strength